Influencing factors of farmers’ participation in domestic waste classification: An empirical analysis based on the semi-nonparametric estimation extended model - Sun, Qianlu; Duan, Huiqing; Zhong, Daojun (Frontiers in Psychology, 2022)
Farmers are the main participants of domestic waste classification, and their willingness and behavior to participate are directly related to the success or failure of domestic waste classification and the construction of “beautiful countryside”. Based on the analysis of the influence mechanism of exemplary behavior and social supervision on farmers’ participation willingness and behavior, an empirical analysis of 988 survey data of farmers in Henan Province is carried out using a semi-non-parametric estimation extended model. The results show that: (1) 85.63% of farmers are willing to participate in the classification of domestic waste, but their willingness and behavior are not consistent. (2) The exemplary behavior of relatives can only increase the willingness of farmers. The exemplary behavior of neighbors and village cadres not only has a positive impact on the behavior, but also facilitates the transformation of willingness to behavior. (3) The supervision of village cadres can increase the willingness of farmers. Although the supervision of villagers and cleaners will reduce the willingness of farmers, it has a significant positive impact on the behavior of farmers. Based on the research conclusions, suggestions are made to play the leading role of village cadres, attach importance to the supervision of villagers and cleaners, broaden publicity channels and strengthen publicity to special groups, improve supporting policies and classification equipment, in order to promote the classification of rural domestic waste.